2017
DOI: 10.1016/j.bbrc.2017.09.092
|View full text |Cite
|
Sign up to set email alerts
|

The hierarchical structure of the perichromosomal layer comprises Ki67, ribosomal RNAs, and nucleolar proteins

Abstract: The perichromosomal layer (PCL) is a structure that surrounds mitotic chromosomes, found in both animal and plant cells. It comprises various proteins and RNAs, mainly derived from the nucleolus. Several functions for the PCL have been suggested; however, the mechanism of PCL organization during mitosis remains unclear. The localization of several nucleolar proteins to the PCL is reportedly dependent on pre-ribosomal RNAs and the marker of proliferation, Ki67, which is a major PCL-localized protein. Here we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 18 publications
6
24
0
Order By: Relevance
“…Consistent with this notion, NOL11 signals in the PR were reduced by the treatment of low-dose actinomycin D, an inhibitor of RNA polymerase I, but hardly affected by the treatment of amanitin, an inhibitor of RNA polymerase II ( Supplementary Figure S5 ). In contrast, Ki67 signals in the PR were not affected by these inhibitors ( Supplementary Figure S5 ) as reported previously ( 20 ). To determine which components possess RNA-binding activity, GST fusion proteins of each component of the NWC complex were purified and tested for their ability to bind to pre-rRNA.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with this notion, NOL11 signals in the PR were reduced by the treatment of low-dose actinomycin D, an inhibitor of RNA polymerase I, but hardly affected by the treatment of amanitin, an inhibitor of RNA polymerase II ( Supplementary Figure S5 ). In contrast, Ki67 signals in the PR were not affected by these inhibitors ( Supplementary Figure S5 ) as reported previously ( 20 ). To determine which components possess RNA-binding activity, GST fusion proteins of each component of the NWC complex were purified and tested for their ability to bind to pre-rRNA.…”
Section: Resultssupporting
confidence: 89%
“…A fractionation experiment conducted on mitotic cell extracts also showed that NOL11 was present in the chromosome-enriched fraction, whereas TIF-IA, another nucleolar protein and rRNA transcription factor, was barely detected (Figure 1D ). These results indicated that NOL11 localized at the PR, which consists of subsets of nucleolar proteins ( 1 , 3 , 15 , 20 , 33 ).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…S9B ). NIFK binds MKI67 and relocalizes to the perichromosome during the mitosis similarly to the rRNA to which NIFK associates during interphase [ 46 , 51 , 52 , 55 ]. Phosphorylation on S666 of HCFC1 has been abundantly identified over the years by mass spectrometry as reported in PSP database (62x on Jan 2020) and is considered downstream of various signaling including ionizing radiation or nocodazole arrest [ 56 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…It might be the case that the removal/addition of a large number of phosphate groups from/to IDRs of RNA-related proteins induces dynamic rearrangements of nucleolus and other RNA-containing nuclear speckles upon the entry of mitosis, which may disrupt these organelle and release a large amount of RNA molecules into the cellular plasm. This will drastically change an intracellular environment, and may affect the assembly/disassembly dynamics of other protein complexes, such as chromosome, which is known to contain preribosomal RNA and nucleolar proteins on the surface (70, 71). It might be the case that chromosome condensation could be induced by orchestrated effects of phosphorylation of chromosome-related proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%